Recasting the Religious Architecture of Islam: The Religious Architecture of Islam I – Asia and Australia and The Religious Architecture of Islam II – Africa, Europe and the Americas (by Hasan-uddine Khan and Kathryn Blair Moore, Eds.) (American Journal of Islam and Society, 2023)
This most recent, and comprehensive compendium, on the subject of the architecture of Islam sheds light on the subject materials. New information on well-known historical examples, the inclusion of historical examples not usually (if ever covered) in such scholarship and an expansion of analysis with respect to modern and contemporary case studies of Islamic religious spaces all underscore the scholarly contribution of this two-volume set. By including such a range of buildings examined, by a large number of scholars from various backgrounds, the compendium effectively recasts the direction of scholarship in this field in a manner that is neither linear or hierarchical.This two-volume set includes 58 essays on a range of regionally-specific examples of architecture from the Islamic world. The first volume of The Religious Architecture of Islam focusses on Asia and Australia, and the second volume focusses on Africa, Europe and the Americas. The volumes are organized in a non-chronological manner, with essays grouped by geographical region covering materials directly related the understanding of religious architecture of Islam.In Volume I, there are four sections with a total of 32 essays written by 29 different scholars. The four sections are: Background themes, West and Central Asia, South and East Asia and Australia.In Volume II, there are four sections with a total of 26 essays written by 20 different scholars. The four sections are: Al-Andalus and the Maghrib, Africa and Sicily, Europe and the Americas.